SOLIDWORKS: Integrated CAM with HSMXpress. - Corbett, Gabriel (linkedin.com, 2018)
Discover Autodesk HSMXpress, the 2.5 axis CAM plugin that brings integrated CAM to SOLIDWORKS. Learn how to set up a machine and fixtures, configure tools, and generate toolpaths.